Dual inhibition of endothelial miR-92a-3p and miR-489-3p reduces renal injury-associated atherosclerosis. (March 2019) - Wiese, Carrie B.; Zhong, Jianyong; Xu, Zhi-Qi; Zhang, Youmin; Ramirez Solano, Marisol A.; Zhu, Wanying; Linton, MacRae F.; Sheng, Quanhu; Kon, Valentina; Vickers, Kasey C.
Abstract: Background and aims: Cardiovascular disease (CVD) is the leading cause of death in chronic kidney disease (CKD) patients, however, the underlying mechanisms that link CKD and CVD are not fully understood and limited treatment options exist in this high-risk population. microRNAs (miRNA) are critical regulators of gene expression for many biological processes in atherosclerosis, including endothelial dysfunction and inflammation. We hypothesized that renal injury-induced endothelial miRNAs promote atherosclerosis. Here, we demonstrate that dual inhibition of endothelial miRNAs inhibits atherosclerosis in the setting of renal injury. Methods: Aortic endothelial miRNAs were analyzed in apolipoprotein E-deficient ( Apoe −/- ) mice with renal damage (5/6 nephrectomy, 5/6Nx) by real-time PCR. Endothelial miR-92a-3p and miR-489-3p were inhibited by locked-nucleic acid (LNA) miRNA inhibitors complexed to HDL. Results: Renal injury significantly increased endothelial miR-92a-3p levels in Apoe −/- ;5/6Nx mice. Dual inhibition of miR-92a-3p and miR-489-3p in Apoe −/− ;5/6Nx with a single injection of HDL + LNA inhibitors significantly reduced atherosclerotic lesion area by 28.6% compared to HDL + LNA scramble (LNA-Scr) controls. To examine the impact of dual LNA treatment on aortic endothelial gene expression, total RNA sequencing was completed, and multiple putative target genes and pathways were identified to be significantly altered, including the STAT3 immune response pathway. Among the differentially expressed genes, Tgfb2 and Fam220a were identified as putative targets of miR-489-3p and miR-92a-3p, respectively. Both Tgfb2 and Fam220a were significantly increased in aortic endothelium after miRNA inhibition in vivo compared to HDL + LNA-Scr controls. Furthermore, Tgfb2 and Fam220a were validated with gene reporter assays as direct targets of miR-489-3p and miR-92a-3p, respectively. In human coronary artery endothelial cells, over-expression and inhibition of miR-92a-3p decreased and increased FAM220A expression, respectively. Moreover, miR-92a-3p overexpression increased STAT3 phosphorylation, likely through direct regulation of FAM220A, a negative regulator of STAT3 phosphorylation. Conclusions: These results support endothelial miRNAs as therapeutic targets and dual miRNA inhibition as viable strategy to reduce CKD-associated atherosclerosis. Graphical abstract: Image 1 Highlights: Aortic endothelial miR-92a-3p levels are increased in a mouse model of renal injury. Dual inhibition of miR-92a-3p and miR-489-3p significantly reduced atherosclerotic lesion area (28.6%) after a week. Dual miRNA inhibition in 5/6Nx; Apoe −/− mice significantly altered TGFβ signaling pathway and STAT3 transcriptional activity. Tgfb2 and Fam220a are novel targets of miR-489-3p and miR-92a-3p, respectively. Within human endothelial cells, miR-92a-3p directly regulates Fam220a, which negatively regulates STAT3 activity.